2018
DOI: 10.1016/j.displa.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of correlated colour temperature on wayfinding: A study in a virtual airport environment

Abstract: This study was designed to explore the effects of lighting's correlated colour temperature (CCT) on wayfinding performance in airports and to compare different CCTs to understand their effects on wayfinding performance. The experiment was conducted in a single phase with the participation of three different groups of university students who experienced the virtual airport environment in three different lighting settings: 3000 K, 6500 K and 12,000 K. The participants were asked to direct the researcher from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…There is no consensus in literature on gender difference affecting spatial abilities. The results of this study are parallel to the results obtained in previous research regarding the gender difference favoring males, affecting wayfinding and spatial navigation performances. However, certain studies in literature have found no gender difference or favored females in spatial performances …”
Section: Discussionsupporting
confidence: 87%
“…There is no consensus in literature on gender difference affecting spatial abilities. The results of this study are parallel to the results obtained in previous research regarding the gender difference favoring males, affecting wayfinding and spatial navigation performances. However, certain studies in literature have found no gender difference or favored females in spatial performances …”
Section: Discussionsupporting
confidence: 87%
“…It can greatly stimulate the users' visual sense and is used in different fields [40]. In the aspect of simulating physical lighting environment, VR is a better choice to replace the physical scene and many scholars have studied the human-factors lighting [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…This is because people feel safest when they have a good overview of the space in which they are moving and if they feel they are supported by other users [ 11 ]. It has been found in the previous literature that outdoor lighting has a significant effect on how a space is perceived and on perceived security [ 12 , 13 , 14 , 15 , 16 ]. Therefore, lighting should be considered an essential design variable in urban design.…”
Section: Introductionmentioning
confidence: 99%